Biochemical behavior in grass subjected to drought and different concentrations of silicon - Souza, Luma Castro de [UNESP]; Melo, Nilvan Carvalho [UNESP]; Mota Siqueira, Jackeline Araujo; Alves Silva, Vicente Filho; Oliveira Neto, Candido Ferreira de (Univ Fed Grande Dourados, 2015)
Corn is a crop that has a great socio-economic importance, however, have suffered from water stress. Stress is considered a significant deviation from the excellent conditions for life, thus silicon (Si) is a chemical element that mitigates this type of stress that culture, as silicon can stimulate growth and crop production through various actions indirect, and thus provides protection against abiotic factors such as water stress, aluminum toxicity, iron and others. The objective of this study was to evaluate the concentration of proteins and amino acids in maize subjected to drought and different concentrations of Si The experiment was conducted in a greenhouse at the Federal Rural University of Amazonia, Campi Captain Wells, PA, Brazil. Maize plants (Zea mays) variety were used PZ 242 The experimental design was completely randomized (CRD), in which two water conditions were evaluated:. Control (without Si) and water deficit (with Si concentration) with four concentrations silicon in the form of sodium metasilicate (0.5, 1.0, 1.5 and 2.0 mu M) with 7 replicates. The plants treated with Si in concentrations of 0.5 mu M and 1.5 mu M increased the retention of water in the leaf tissue. Concentrations of total soluble proteins in roots and leaves of corn plants decreased significantly when they were subjected to water stress. While the concentrations of soluble amino acids in the roots of plants subjected to stress S / Si, 0.5 mu M stress and stress have increased 1.0 mu M. However, the concentrations of soluble amino acids in leaves increased in all treatments. Moreover, water stress significantly affected the biochemical processes in corn plants.
Keywords: water stress; abiotic factors; biochemical processes